Navigating Political Landscapes: Overcoming Geopolitical Adversaries in Nepal's Development Diplomacy - Khanal, Gopal (NCWA Annual Journal, 2023)
Nepal has achieved remarkable economic and social progress over the past two decades, but it still faces daunting challenges. The country is still wrestling with poverty, unemployment, and inequality. Its infrastructure remains inadequate, and it lacks the necessary human capital and resources to launch a sustained economic and social development program. Nepal's political system is still in transition, with the new constitution still being implemented. The Nepali government is committed to implementing the constitution and has taken steps to establish a federal system of government. The government must continue to prioritize economic and social development for achieving a prosperous future for the country and its people. This should include investments in infrastructure, human capital, and the productive sectors. The government must ensure political stability, which is essential for the country to attract foreign investment and foster economic growth. Nepal has to take advantage of its geopolitical position, with its unique position in between two powerful and important countries- India and China. Nepal’s relationship with both countries is important and should be developed further. Nepal can use its diplomatic relations and leverage to strengthen bilateral ties with both countries and build cooperation, which in turn can be used to promote the development of Nepal. Nepal should focus on building its capacity and expertise in the field of development and diplomacy. Nepal should look to further strengthen its ties with development partners such as the United Nations, World Bank, and other financial institutions. What are the challenges and opportunities of development diplomacy in Nepal? How can the shifting global geopolitical order impact Nepal's endeavors toward development diplomacy? This research revisits the prospects and challenges of Nepal's development diplomacy in the changing global geopolitical order based on a desk study.